Formaldehyde contamination in seafood industry: an update on detection methods and legislations - Mehta, Naresh Kumar; Vaishnav, Anand; Priyadarshini, Mocherla Bhargavi; Debbarma, Payel; Hoque, Mohammad Sazedul; Mondal, Pronoy; Bono, Gioacchino; Koirala, Pankaj; Kettawan, Aikkarach; Nirmal, Nilesh Prakash; Mahmud Ab Rashid, Nor-Khaizura (Springer, 2024)
Seafood is abundant in high-quality protein, healthy fats (n-3 and n-6 PUFAs), minerals (calcium, magnesium, copper, selenium, and so on), and vitamin D. Functional compounds in seafood can protect against lifestyle-related diseases. Having had all the merits mentioned, it is also a highly putrefable food item. To maintain quality and prolong seafood’s shelf life, various chemicals have been added, including nitrite, sulfur dioxide, and formaldehyde. In this review, we summarize the uses, the incidence of added formalin contamination, and the approved limit for seafood products. Additionally, worldwide regulations or standards for the use of formalin in seafood products, as well as recent changes relevant to new methods, are highlighted. Although strict limits and regulations have been placed on the utilization of formaldehyde for seafood preservation, there are few incidences reported of formalin/formaldehyde detection in seafood products around Asian countries. In this context, various qualitative and quantitative detection methods for formaldehyde have been developed to ensure the presence of formaldehyde within acceptable limits. Besides this, diferent rules and regulations have been forced by each country to control formaldehyde incidence. Although it is not an issue of formaldehyde incidence in European countries, strict regulations are implemented and followed.